Thymectomy in Myasthenia Gravis: The Short-Term Outcome at a Tertiary Center in Nepal (Birat Journal of Health Sciences, 2025)
Introduction: Myasthenia gravis is a common autoimmune condition that primarily affects women and typically present with symptoms ranging from ocular muscle weakness to severe generalize muscle fatigue. Thymectomy has been shown to improve outcomes by reducing both complications and mortality.  This study evaluates short-term outcome of the patients who underwent thymectomy.Methods: A retrospective cohort study was conducted at Nobel Medical College and Teaching Hospital, including patients admitted between March 2021 and December 2024. Patient records were reviewed using a structured questionnaire. Data were entered in Epi-data (Version 3.1) and analyzed using SPSS (Version 20). Ethical approval was obtained from the Institutional Review Committee.Results: The study included 22 Myasthenia gravis patients, with a mean age of 33.7 years (range: 17–55 years), the majority of whom were female with normal BMI. Thyroid disorders being the most common comorbidities. Most patients presented with classic MG symptoms such as ophthalmoplegia, bulbar involvement, limb weakness, and respiratory issues. Following thymectomy, Thymic hyperplasia being most common pathology, 86.3% were weaned off prednisolone, and 86.4% had reduced pyridostigmine doses. The mean pyridostigmine dose decreased from 280 ± 88.8 mg preoperatively to 128.2 ± 105.3 mg postoperatively. Complete cessation of pyridostigmine was achieved in 36% patients, while 31% had a half reduction, 27% had a quarter reduction with significant symptomatic improvement.Conclusions: In conclusion, thymectomy in myasthenia gravis shows a better outcome with improvement in symptoms and reduction in medication.